Correlating the role of hydrophilic/hydrophobic nature of Rh(I) and Ru(II) supported organosilica/silica catalysts in organotransformation reactions - Lazar, Anish; George, Shoy C.; Jithesh, P. R.; Vinod, C. P.; Singh, A. P. (Applied Catalysis A-General, 2016)
Highly reactive and hydrophobic triphenyl phosphine based rhodium(I) and ruthenium(II) organometallic complexes over benzene containing periodic mesoporous organosilica (PMOB) have been synthesized. This has been achieved by the immobilization of neat metal complexes like RhCl(PPh3)(3) [Wilkinson catalyst], RuHCl(CO)(PPh3)(3) and RuCl2(PPh3)(3) over aminofunctionalized PMOB to get RhCl(PPh3)(2)-PrNH2PMOB, RuHCl(CO)(PPh3)(2)-PrNH2PMOB and RuCl2(PPh3)(3)-PrNH2PMOB, respectively. The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption analyses, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, SEM, TEM and contact angle measurements. The XRD and N-2 sorption analyses showed excellent textural properties with ordered mesoporous channel structure of all synthesized catalysts. The organic moieties anchored in PMOB were confirmed by C-13 CPMAS NMR and Fr-IR spectroscopy with Si-29 CPMAS NMR spectroscopy providing the information about the degree of functionalization of surface silanol groups with organic moiety. The Rh(I) and Ru(II) complexes supported on MCM-41/SBA-15/PMOE (ethane-PMO) were synthesized, and their catalytic activities in hydrogenation and sulfoxidation reactions were compared with Rh(I) and Ru(II) complexes supported on PMOB. The results show that PMOB based catalysts exhibit higher activities and selectivities than MCM-41/SBA-15/PMOB supported catalysts, neat homogeneous complexes and without catalyst. The better catalytic performance of PMOB based catalyst is attributed to the hydrophobic nature and high surface area of the PMOB support. The recycling studies of anchored catalysts show no major deactivation of the catalyst. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heterogeneous catalysts; Hydrogenation and sulfoxidation; Hydrophobic; Periodic mesoporous organosilica